Chemotherapy followed by low dose radiotherapy in childhood Hodgkin's disease: retrospective analysis of results and prognostic factors - Viani, Gustavo A (BioMed Central, 2006)
PURPOSE: To report the treatment results and prognostic factors of childhood patients with Hodgkin's disease treated with chemotherapy (CT) followed by low dose radiotherapy (RT). PATIENTS AND METHODS: This retrospective series analyzed 166 patients under 18 years old, treated from January 1985 to December 2003. Median age was 10 years (range 2–18). The male to female ratio was 2,3 : 1. Lymphonode enlargement was the most frequent clinical manifestation (68%), and the time of symptom duration was less than 6 months in 55% of the patients. In histological analysis Nodular Sclerosis was the most prevalent type (48%) followed by Mixed Celularity (34.6%). The staging group according Ann Arbor classification was: I (11.7%), II (36.4%), III (32.1%) and IV (19.8%). The standard treatment consisted of chemotherapy multiple drug combination according the period of treatment protocols vigent: ABVD in 39% (n-65) of the cases, by VEEP in 13 %(n-22), MOPP in 13 %(n-22), OPPA-13 %(n-22) and ABVD/OPPA in 22 %(n-33). Radiotherapy was device to all areas of initial presentation of disease. Dose less or equal than 21 Gy was used in 90.2% of patients with most part of them (90%) by involved field (IFRT) or mantle field. RESULTS: The OS and EFS in 10 years were 89% and 87%. Survival according to clinical stage as 94.7%, 91.3%, 82.3% and 71% for stages I to IV(p = 0,005). The OS was in 91.3% of patients who received RT and in 72.6% of patients who did not (p = 0,003). Multivariate analysis showed presence of B symptoms, no radiotherapy and advanced clinical stage to be associated with a worse prognosis. CONCLUSION: This data demonstrating the importance of RT consolidation with low dose and reduced volume, in all clinical stage of childhood HD, producing satisfactory ten years OS and EFS. As the disease is highly curable, any data of long term follow-up should be presented in order to better direct therapy, and to identify groups of patients who would not benefit from radiation treatment.